2009
DOI: 10.1051/0004-6361/200912087
|View full text |Cite
|
Sign up to set email alerts
|

Dust amorphization in protoplanetary disks

Abstract: Aims. High-energy irradiation of circumstellar material might impact the structure and the composition of a protoplanetary disk and hence the process of planet formation. In this paper, we present a study of the possible influence of stellar irradiation, indicated by X-ray emission, on the crystalline structure of circumstellar dust. Methods. The dust crystallinity is measured for 42 class II T Tauri stars in the Taurus star-forming region using a decomposition fit of the 10 μm silicate feature, measured with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
1
22
2
Order By: Relevance
“…Above this luminosity value no trend is visible. Still, we observe that objects with high X-ray luminosities seem to have higher crystalline fractions, which seems at first in contradiction with the conclusion by Glauser et al (2009). Given the limited number of objects for which we have X-ray data in our sample, however, we were not able to perform any age selection as in Glauser et al (2009).…”
Section: Silicate Crystallization and Amorphizationcontrasting
confidence: 85%
See 2 more Smart Citations
“…Above this luminosity value no trend is visible. Still, we observe that objects with high X-ray luminosities seem to have higher crystalline fractions, which seems at first in contradiction with the conclusion by Glauser et al (2009). Given the limited number of objects for which we have X-ray data in our sample, however, we were not able to perform any age selection as in Glauser et al (2009).…”
Section: Silicate Crystallization and Amorphizationcontrasting
confidence: 85%
“…This study shows that, obviously, the accretion activity may have a strong impact on the dust chemistry in circumstellar disks. Recently, Glauser et al (2009) identified an anti-correlation between X-ray luminosity of the stars and crystalline fraction for the warm disk component (C warm in Sect. 3.2).…”
Section: Silicate Crystallization and Amorphizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Once again, we run the Kendall τ test, and find essentially no significant correlation in the warm disk regions (τ = −0.27, p = 0.10) and the colder parts of the disks (τ = −0.02, p = 0.88). Glauser et al (2009) suggested that irradiation of dust grains by energetic ions from the stellar winds of young stars can amorphize the surface layer of the protoplanetary dust very efficiently, thus erasing any correlation between crystalline mass fraction and stellar parameters, such as bolometric luminosity, effective temperature, accretion rate, or disk geometry. Ábrahám et al (2009) discovered that episodes of increased accretion may create new crystals.…”
Section: (B) Dust Properties Of Disks Around Cool T Tauri Starsmentioning
confidence: 99%
“…Dolginov & Stepinski (1993) argue that the magnetic field will diffuse the cosmic rays paths through the atmosphere and, hence, decrease the critical column density (or scale height) λ CR for cosmic ray attenuation. Glauser et al (2009) demonstrate that fast protons and He ions interact with dust grains in disks, hence, the dust will decrease the effective attenuation length in the atmosphere further. This suggests that a smaller fraction of the atmosphere and of the cloud is influenced by cosmic rays.…”
Section: Cosmic Ray Attenuationmentioning
confidence: 93%